Hexachlorobenzene Induces Deregulation of Cellular Growth in Rat Liver - Giribaldi, María Laura (2011)
Hexachlorobenzene (HCB) is an organochlorine pesticide widely distributed in the biosphere. The aim of the present study was to investigate the effect of HCB on the homeostasis of liver cell growth, analyzing parameters of cell proliferation and apoptosis, in HCB (0.1, 1, 10 and 100. mg/kg body weight)-treated rats, during 4 weeks. Cell proliferation and ERK1/2 phosphorylation, associated with survival mechanisms, were increased at HCB 100. mg/kg. The pesticide increased the number of apoptotic cells, and the activation of caspase-3, -9 and -8, in a dose-dependent manner, suggesting that HCB-induced apoptosis is mediated by caspases. Increased Fas and FasL protein levels indicate that the death receptor pathway is also involved. This process is associated with decreased Bid, and increased cytosolic cytochrome c protein levels. Transforming growth factor-beta1 (TGF-β1) intervenes in apoptotic and/or proliferative processes in hepatocytes. TGF-β1 cDNA and protein levels are dose-dependently increased, suggesting that this cytokine might be involved in HCB-induced dysregulation of cell proliferation and apoptosis. In conclusion, this study reports for the first time that HCB induces loss of the homeostatic balance between cell growth and cell death in rat liver. Induced apoptosis occurs by mechanisms involving signals emanating from death receptors, and the mitochondrial pathway.